Persepsi Mahasiswa Tentang Kontroversial Anggota Dewan Penasihat Danantara Thaksin Shinawatra - Emilianshah Banowo; Muhamad Rafli (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Budget efficiency is a measure taken by the government to achieve development goals and public welfare. Amidst the issue of budget efficiency, the presence of Danantara raises critical questions. Danantara was established with the aim of strengthening the Indonesian economy and investing to create prosperity for all Indonesians. However, the public associates the funds cut through budget efficiency with being redirected to Danantara. The selection of controversial figures such as Thaksin Shinawatra also attracted attention. This study aims to investigate Generation Z students' perceptions of the controversial Danantara Advisory Board member Thaksin Shinawatra, with a focus on Generation Z students at Gunadarma University. This study employs a qualitative approach based on the constructivist paradigm, utilizing the social construction theory of L. Berger and Luckmann. Data was collected through in-depth interviews, observations, and documentation of several informants. The results of the study indicate that Generation Z students at Gunadarma University have a high level of political awareness and are critical of Danantara's existence. Negative perceptions arise due to figures who are considered untrustworthy, a lack of institutional transparency, and the involvement of controversial figures such as Thaksin Shinawatra. This study concludes that Generation Z students at Gunadarma University's perceptions of Danantara reflect increasing demands for a more open, participatory, and accountable government in the management of national policies and resources.